Tinjauan Atas Strategi Komunikasi Pemasaran Melalui Media Sosial Instagram Pada Dinas Perdagangan Dan Perindustrian Kota Bogor - Rosadi, Reysi Resmidianti; Mulyana, Mumuh; Zuhdi, Saefudin (Jurnal Informatika Kesatuan, 2023)
Economic growth is an important indicator of the success of national development. In terms of national economic growth, small and medium industries (IKM), which are also part of micro, small and medium enterprises (MSMEs), are considered capable of playing an important role in driving economic growth. The use of social media is spreading faster than ever before. One of the goals of social media is in the application of marketing communications. To advance the products of Small and Medium Industries in the City of Bogor, of course, cannot be separated from the role of more attractive and dynamic marketing communications.The research objectives are: 1) To find out the marketing communication strategy for small and medium industrial products through Instagram social media at the Bogor City Trade and Industry Service; 2) To find out the obstacles in implementing the marketing communication strategy for small and medium industry products through Instagram social media at the Bogor City Trade and Industry Service; 3) To find out efforts to deal with obstacles in implementing marketing communication strategies for small and medium industrial products through Instagram social media at the Bogor City Trade and Industry Service.The results of the study show that: 1) Social Media, Instagram is very well managed by the Department of Trade and Industry in providing information and interesting content from Small and Medium Industry products in the city of Bogor; 2) The obstacle faced is the difficulty of increasing insight to reach Instagram users outside of the Instagram account followers of the Bogor City Trade and Industry Service; 3) As for efforts to deal with obstacles, namely trying to publish content related to Small and Medium Industry products more often and to be accurate in providing information related to these IKM products.Keywords: Marketing Communication, Social Media Instagram, IKM